Protection Effect of Endomorphins on Advanced Glycation End Products Induced Injury in Endothelial Cells - Jing Liu; Liping Yan; Ruilan Niu; Limin Tian; Qi Zhang; Jinxing Quan; Hua Liu; Suhong Wei; Qian Guo (Journal of Diabetes Research)
Endomorphins (EMs) have a very important bridge-function in cardiovascular, endocrinological, and neurological systems. This study is to investigate the effects of EMs on the synthesis and secretion of vasoactive substances induced by advanced glycation end products in primary cultured human umbilical vein endothelial cells (HUVECs). Firstly, HUVECs were stimulated with AGEs-bovine serum albumin (AGEs-BSA), bovine serum albumin (BSA), or both AGEs-BSA and EMs together, respectively. Then, HUVEC survival rate was calculated by MTT assay, the levels of NO, endothelial nitric oxide synthase (eNOS), and inducible nitric oxide synthase (iNOS) were detected by colorimetric analysis, and the contents of endothelin-1 (ET-1) were detected by ELISA. The mRNA levels of eNOS and ET-1 were measured by RT-PCR. The expression of p38 mitogen-activated protein kinase (p38 MAPK) was detected by immunofluorescence assay. The results showed that the mRNA expression and secretion of eNOS were significantly enhanced after incubation with EMs compared to those with AGEs-BSA, while the secretion of NO and iNOS, mRNA expression, and secretion of ET-1 had opposite changes. The fluorescence intensity of p38MAPK in nuclear was decreased after pretreatment with EMs compared to incubation with AGEs-BSA. Conclusion. The present study suggests that EMs have certain protection effect on AGEs-BSA-induced injury in HUVEC.